Cytomegalovirus post kidney transplantation: prophylaxis versus pre‐emptive therapy?. (27th July 2015) - Fehr, Thomas; Cippà, Pietro E.; Mueller, Nicolas J.
Summary: Cytomegalovirus is the most important pathogen causing opportunistic infections in kidney allograft recipients. The occurrence of CMV disease is associated with higher morbidity, higher incidence of other opportunistic infections, allograft loss and death. Therefore, an efficient strategy to prevent CMV disease after kidney transplantation is required. Two options are currently available: pre‐emptive therapy based on regular CMV PCR monitoring and generalized antiviral prophylaxis during a defined period. In this review, we describe those two approaches, highlight the distinct advantages and risks of each strategy and summarize the four randomized controlled trials performed in this field so far. Taken this evidence together, pre‐emptive therapy and anti‐CMV prophylaxis are both equally potent in preventing CMV‐associated complications; however, the pre‐emptive approach may have distinct advantages in allowing for development of long‐term anti‐CMV immunity. We propose a risk‐adapted use of these approaches based on serostatus, immunosuppressive therapy and availability of resources at a particular transplant centre.